Influence of DNA geometry on transcriptional activation in Escherichia coli. - Déthiollaz, S (1996)
Transcription from many Escherichia coli promoters can be activated by the cAMP-CRP complex bound at different locations upstream of the promoter. At some locations the mechanism of activation involves direct protein-protein contacts between CRP and the RNA polymerase. We positioned the CRP binding site at various distances from the transcription start site of the malT promoter and measured the in vivo activities of these promoter variants. From the activation profiles we deduce that the protein-protein interactions involved in transcriptional activation are rather rigid. A heterologous protein (IHF) that bends the DNA to a similar degree as does CRP activates transcription when bound at sites equivalent to activating positions for CRP. DNA geometry makes a major contribution to the process of transcriptional activation and DNA upstream of the activator binding site participates in this process. Removal of this DNA decreases the capacity of the malT promoter to be activated by CRP in vitro. We conclude that both DNA topology and direct protein-protein contacts contribute to transcriptional activation and that the relative importance of these two modes of activation depends on the nature of the activator and on the location of the activator binding site.